INCORPORACIÓN EN EL CÓDIGO ORGÁNICO GENERAL DE PROCESOS PARA LA HOMOLOGACIÓN, RECONOCIMIENTO Y EJECUCIÓN DE LOS LAUDOS ARBITRALES EXTRANJEROS EN EL ECUADOR. - Carrillo Chumbe., Génesis Andrea (2021)
The present thesis is entitled "Incorporation in the General Organic Code of Proceedings for the homologation, recognition and enforcement of foreign arbitral awards in Ecuador", and the need for its implementation arises due to an analysis of the General Organic Code of Proceedings in Chapter VII, which includes from Article 102 to 106 on judgments, arbitral awards, and mediation acts issued abroad, in which the Organic Law for the Promotion of Production, Attraction of Investments, Generation of Employment, and Stability and Equilibrium in Ecuador, The Organic Law for the Promotion of Production, Attraction of Investments, Generation of Jobs and Fiscal Stability and Balance by means of the second derogatory provision of 21 August 2018 specifically eliminated the words "arbitral award"; This means that when it comes to resolving this type of conflict and the arbitration award is chosen, it is required that there is due homologation and recognition for these to have the validity that concerns them respectively, since with regard to a way of resolving a conflict it is intended that arbitration awards are also part of a conflict solution so it is a decision issued by arbitrators appointed for specific cases or by relevant arbitration bodies to which the parties have submitted, For a long time and before the new reforms of the General Organic Code of Procedure, arbitral awards issued abroad were subject to a process of recognition and homologation so that they could then be enforced. In addition, materials and methods were applied to develop this research, and interviews and surveys were carried out with legal professionals, which have helped me to propose a legal reform project to the General Organic Code of Procedure, to guarantee the rights of the procedural parties with respect to the recognition, approval and enforcement of arbitral awards issued abroad.